Association of cognitive activity and neurocognitive function in blacks and whites with HIV. (28th January 2017) - Krueger, Kristin R.; Adeyemi, Oluwatoyin; Leurgans, Sue; Shah, Raj C.; Jimenez, Antonio D.; Ouellet, Lawrence; Landay, Alan L.; Bennett, David A.; Barnes, Lisa L.
Abstract : Objective: Older persons with HIV are at risk for impaired cognition, yet there is limited information on modifiable factors associated with neurocognitive function in this group. Design: This is a cross-sectional observational study of cognitive activities and neurocognitive function. Methods: We examined the relation between frequency of cognitive activity and current neurocognitive performance in 176 older persons with HIV [70% African American, 76% men; mean age = 58.7 (SD = 5.5); mean education = 13.2 (SD = 2.8)]. Results: In linear regression models adjusted for demographic variables, we found that higher frequency of cognitive activity was associated with better cognition in global cognition, semantic memory, and perceptual speed. Subsequent models that examined the role of race demonstrated that the association was significant only among Blacks for global cognition, episodic memory, working memory, and perceptual speed (interaction of cognitive activity by race: Estimate range = 0.38–0.55; all P < 0.05). Conclusion: Greater frequency of cognitive activity is associated with better neurocognitive function in older persons with HIV, particularly older Blacks. Longitudinal studies are needed to assess the relation of cognitive activity to change in neurocognitive function in older persons with HIV.